Islam and Palestine: The Rise of Ideology in the Midst of Conflict - Rasyid, Muhammad Akmal; Najib, Ahmad Nasi'n; Ibrahim, Maulana Malik (El-Suffah: Jurnal Studi Islam, 2024)
The article aims to examine the escalation of the rise of Islamic ideology in Palestine after previously being threatened with dimming due to the fall of Ottoman Turkey. Then new ideologies such as nationalism, secularism, and communism were born that made Muslims skeptical of their own ideology. This research uses literature study methods, political and historical approaches. The results of the study explain the ideology that developed in the mid-19th century that influenced global political currents. how great was the impact of the collapse of Ottoman Turkey on the fall of Palestine and the dimming of Islamic ideology. The reality of Islamic ideology that contributes greatly to the struggle for Palestinian independence. After a long journey, Islamic ideology has given us concrete proof that this ideology will always exist and is capable of compromising global political dynamics. Abstrak:. Artikel bertujuan untuk mengkaji eskalasi kebangkitan ideologi Islam di Palestina setelah sebelumnya terancam redup akibat jatuhnya Turki Ottoman. kemudian lahirlah ideologi baru seperti nasionalisme, sekularisme, komunisme yang membuat umat Islam skeptis terhadap ideologi mereka sendiri. penelitian ini menggunakan metode studi pustaka, pendekatan politik dan sejarah. hasil penelitian menjelaskan mengenai ideologi yang berkembang pada pertengahan abad ke-19 yang mempengaruhi arus politik global. bagaimana besarnya dampak runtuhnya Turki Utsmaniyah terhadap jatuhnya Palestina dan redupnya ideologi Islam. Realitas ideologi Islam yang berkontribusi besar terhadap perjuangan kemerdekaan Palestina. Setelah perjalanan panjang, ideologi Islam telah memberi kita bukti nyata bahwa ideologi ini akan selalu ada dan mampu berkompromi dengan dinamika politik global. Kata kunci: Ideologi, Turki Ottoman, Palestina